2008
DOI: 10.1074/jbc.m709357200
|View full text |Cite
|
Sign up to set email alerts
|

Specific Citrullination Causes Assembly of a Globular S100A3 Homotetramer

Abstract: S100A3 is a unique member of the Ca 2؉ -binding S100 protein family with the highest cysteine content and affinity for Zn 2؉ . This protein is highly expressed in the differentiating cuticular cells within the hair follicle and organized into mature hair cuticles. Previous studies suggest a close association of S100A3 with epithelial differentiation, leading to hair shaft formation, but its molecular function is still unknown. By two-dimensional PAGE-Western blot analyses using a modified citrulline antibody,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 42 publications
(70 reference statements)
2
70
0
Order By: Relevance
“…S100A3 is overexpressed in head and neck cancer, colorectal cancer, bladder cancer, gastric cancer, and astrocytic tumors, but has an inverse correlation to breast cancer progression (Lloyd et al, 1996;Camby et al, 2000;Yao et al, 2007;Liu et al, 2008Liu et al, , 2013Tyszkiewicz et al, 2014). It is also highly expressed in hair root cells, and is thought to have a role in epithelial cell differentiation and Ca 2+ -dependent hair cuticular barrier formation (Kizawa et al, 2008). The present study demonstrated that subcutaneous injection with anti-S100A3 antibody led to hair growth retardation and a reduced number of hair follicles (Figures 3-5).…”
Section: Discussionmentioning
confidence: 99%
“…S100A3 is overexpressed in head and neck cancer, colorectal cancer, bladder cancer, gastric cancer, and astrocytic tumors, but has an inverse correlation to breast cancer progression (Lloyd et al, 1996;Camby et al, 2000;Yao et al, 2007;Liu et al, 2008Liu et al, , 2013Tyszkiewicz et al, 2014). It is also highly expressed in hair root cells, and is thought to have a role in epithelial cell differentiation and Ca 2+ -dependent hair cuticular barrier formation (Kizawa et al, 2008). The present study demonstrated that subcutaneous injection with anti-S100A3 antibody led to hair growth retardation and a reduced number of hair follicles (Figures 3-5).…”
Section: Discussionmentioning
confidence: 99%
“…The deimination of trichohyalin catalyzed by PAD3 is crucial for the properties of trichohyalin, as well as for S100A3, another major protein of the hair follicles (Tarcsa et al, 1996(Tarcsa et al, , 1997Steinert et al, 2003;Kizawa et al, 2008). Thereby, PAD3 is likely to play a major role in the establishment of the mechanical resistance of cells in the hair follicles and particularly in the hair shaft.…”
Section: Deimination and Peptidylarginine Deiminases In Skin Physiologymentioning
confidence: 99%
“…PAD2 is thought to play a role in the onset and progression of neurodegenerative human disorders, including Alzheimer disease and multiple sclerosis, and it has also been implicated in glaucoma pathogenesis (Bhattacharya et al, 2006;Moscarello et al, 2007;Cafaro et al, 2010). Human PAD3 modulates hair follicle structural proteins, such as trichohyalin and S100A3 in the inner root sheath (Rogers et al, 1997;Kanno et al, 2000;Kizawa et al, 2008). Together with the PAD1 enzyme, PAD3 may also play a role in terminal differentiation of the epidermis (Senshu et al, 1996;Méchin et al, 2007).…”
Section: Peptidylarginine Deiminase Familymentioning
confidence: 99%
See 1 more Smart Citation
“…4) Peptidylarginine deiminase (PADI) converts several arginine residues of S100A3 protein to citrullines within immature cuticular cells. 5) Genetic mutations including hair-dominant PADI isotype (PADI3) have recently been shown to cause uncombable hair syndrome.…”
mentioning
confidence: 99%